Epstein Barr Virus Positivity and Behavioral Patterns in Nasopharyngeal Cancer Patients Presenting in Oncology Ward at JPMC, Karachi: Epstein Barr Virus Positivity in Nasopharyngeal Cancer Patients - Nasir, Sana; Haider, Ghulam; Jabeen, Mehwish; Mughis, Zubair; Babar Khan, Tuba; Zahoor, Saima; Sami, Ahra; Rani, Berkha; Sehar, Sana (Pakistan Journal of Health Sciences, 2024)
Immunohistochemistry tests for the presence of the Epstein-Barr virus latent membrane protein (EBV-LMP), which can be used to diagnose non-Hodgkin’s lymphoma. Tumors expressing high amounts of latent membrane protein 1 (LMP-1) provide more evidence that EBV is an etiologic agent in the development of non-Hodgkin lymphoma. Objective: To investigate the association between Epstein-Barr Virus infection and Nasopharyngeal Cancers within a cohort of 131 patients. Methods: A prospective, observational approach was employed, gathering demographic data, addiction profiles, clinical stages, histopathological types, and Epstein-Barr Virus status through patient interviews and medical records review. Polymerase chain reaction assisted in the detection of the Epstein Barr Virus in paraffin-embedded tissue slices that had been treated with formalin. Results: Among the participants, 92 (70.2%) tested positive for Epstein-Barr Virus infection. Notably, 49.6% of Epstein-Barr Virus-positive individuals were active smokers, and 64.9% were treatment-naive. Epstein-Barr Virus positivity was prevalent in stage II (40.5%) and stage III (35.1%) nasopharyngeal cancer patients. Conclusions: It was concluded that understanding the role of the Epstein-Barr Virus and associated risk factors in nasopharyngeal cancer development is crucial for targeted interventions and preventive measures. Further research could enhance our understanding of Epstein-Barr Virus-associated cancers and inform prospective intervention methods.